Choice, control, and animal welfare: definitions and essential inquiries to advance animal welfare science - Englund, Maisy D.; Cronin, Katherine A. (Frontiers in Veterinary Science, 2023)
The ways in which humans can support 'good welfare' for animals in their care is an ongoing subject of debate: some place emphasis on the animals' physical health; others, on animals' ability to live 'natural lives;' and others on animals' affective states or psychological wellbeing. Recently, there has been an increase in interest in how an animal's ability to exercise control over its environment could impact their welfare. In this article, we take the stance that the relevant aspects of the first two concepts of animal welfare (physical health, natural lives) are largely addressed when an animal's psychological wellbeing is prioritized. Through that lens, we review the current state of the literature regarding the psychology of control, and the intersection between choice, control, and welfare. We clarify terms to support future work, and propose future directions that could lead to a better understanding of the psychological benefits of choice and control and ultimately inform animal care decisions.The multidimensional concept of 'animal welfare'The concept of animal welfare is a complicated one. There is some philosophical controversy about how welfare should be defined, and care for an animal can differ dramatically depending upon which definition of welfare one adopts (Fraser, 2008).Veterinarians and farmers have historically placed emphasis on animals' physical health in conceptions of welfare (e.g.,